Proportions of Women in STEM Leadership in the Academy in the USA - Laura McCullough (MDPI AG, 2019)
A considerable body of research exists on women in leadership and likewise, on women in STEM (science, technology, engineering, mathematics) fields. However, the intersection of the two is terra incognita: women in leadership in STEM. At the most fundamental level, we do not even have a solid idea of how many women hold leadership positions in STEM. This study determined the proportion of women in leadership positions in several academic STEM areas via a sampling of institutions across the United States. In every area studied, women held fewer leadership positions than the proportion of female PhDs in those fields. The proportion of women in non-STEM specific top academic leadership roles was also examined to see what proportion of those individuals leading academic institutions might have background in a STEM discipline and how that compares to men in the same positions.